Contrasting FOR and WITH factor chains: The case of material supply chains and human factor chains in Guatemalan nongovernmental organizations. Issue 2 (17th October 2018) - Helms, Marilyn M.; LeMay, Stephen A.; Dwyer, Michael J.
Abstract : Nongovernmental organizations (NGOs) have varied success in meeting the challenges of disasters in Antigua, Guatemala. This research uses the TO–FOR–WITH model based on nine criteria that separate surviving NGOs from transient NGOs. Two Guatemalan NGOs, Corazon de los Nino and Sonidos para la Vida, are used to validate the model. The two NGOs differ on three of the nine criteria in the TO–FOR–WITH model. Corazon meets all nine criteria and is considered a WITH organization using local sources for employment, supplies, and logistics. Sonidos is a FOR organization because it falls short in the three categories of bilateral communication, residual intelligence, and post hoc deployment. The criteria were found to distinguish the two NGOs in meaningful ways. However, two cases are not sufficient for theory building. We distinguish between factor chains and material supply chains, a distinction that is especially salient for humanitarian services, which are the primary offerings of many NGOs. No prior studies have tested this recent model and no previous studies have addressed the distinction between material supply chains and factor chains. Additional research is needed including expanding to other NGOs, other countries, and other settings.